Predicting hearing aid acceptance and beyond - KARCZEWSKA–NABELEK, Anna (Archives of Acoustics, 2007)
The acceptable noise level (ANL) procedure was developed to quantify the maximum amount of background noise that listeners are willing to accept while listening to speech. The ANL is calculated as a difference between a listener's most comfortable listening level (MCL) for speech and the maximum acceptable noise level (BNL). Successful hearing aid use is related to an individual's ability to accept background noise. A formula was developed to calculate the probability of success with hearing aids as a function of individual ANL. Research has demonstrated that ANLs with and without hearing aids are highly correlated, and the ANL test can predict hearing-aid use with 85% accuracy. Several interesting issues have emerged from recent ANL investigations: 1) How should a patient be counseled regarding the ANL? 2) What factors contribute to the large inter-subject variability of ANL? 3) If successful hearing aid use relates to the ability to accept background noise, can this ability be enhanced by auditory training or pharmacological means? 4) Can hearing aids with advanced processing features, such as noise reduction, allow occasional or unsuccessful hearing aid users to become successful users?